Lipases efficiently stearate and cutinases acetylate the surface of arabinoxylan films - Stepan, A. M. (2013)
This is the first report on successful enzyme catalyzed surface esterification of hemicellulose films. Enzyme catalyzed surface acetylation with vinyl acetate and stearation with vinyl stearate were studied on rye arabinoxylan (AX) films. Different surface analytical techniques (FT-IR, TOF-SIMS, ESCA, CA) show that lipases from Mucor javanicus, Rhizopus oryzae and Candida rugosa successfully surface stearate AX films and that a cutinase from Fusarium solani pisi surface acetylates these films. The specificities of cutinase and lipases were also compared, and higher activity was observed for lipases utilizing long alkyl chain substrates while higher activity was observed for cutinase utilizing shorter alkyl chain substrates. The contact angle analysis showed films with increased initial hydrophobicity on the surfaces.